Optimizing Students' Critical Thinking Skills Through Conservation-Based Ethno-Inquiry Practical Guide - Dewi, Ika Nurani; Sukri, Akhmad; Fajri, Siti Rabiatul; Ayu, Ieke Wulan (Biosfer: Jurnal Pendidikan Biologi, 2025)
This study aims to develop and produce a high-quality (valid, practical, and effective) ethno-inquiry practical guide to train students' critical thinking skills. This research is developmental and uses the R&D model. The teaching material developed was applied to 85 students from the Biology Education Department. The analysis of the practical guide's quality was conducted using average validity scores, Cronbach's alpha coefficient, paired t-test, N-gain, and ANOVA tests. The results show that the ethno-inquiry practical guide meets the following criteria: 1) valid based on content and construct validity reviews, 2) practical for use in learning, as indicated by excellent implementation of learning activities, and 3) effective in enhancing students' critical thinking skills with scores ranging from 0.40-0.52 (medium category). Based on student responses, the ethno-inquiry practical guide is categorized as good. This research implies that the practical guide can serve as an innovative solution to improve students' critical thinking skills.